PERBANDINGAN SIFAT KIMIA AIR SUNGAI CISADANE PADA TATA GUNA LAHAN YANG BERBEDA - Desy Rosarina; Ellysa Kusuma Laksanawati (Prosiding Simposium Nasional Multidisiplin (SinaMu), 2019)
The study that examined the analysis of the chemical properties of the Cisadane River in Tangerang City was carried out from April to June 2019, to compare the water quality of the Cisadane river through chemical properties in three types of land use. The study used a survey method by determining the sampling of the test material and measuring water quality carried out by purposive sampling, adjusted for the sinking of the land. Sampling points for fisheries area and housing areas are in Karawaci Hilir (station 1), Babakan (station 2) and Sukajadi (station 3). The sampling point of the factory area is around the tofu mill (station 1), the paper mill (station 2) and the palm oil mill (station 3) all in Karawaci Hilir. Data analysis in the laboratory includes DO, COD, BOD and PO4. The results showed that water quality in the catchment area of fishermen had DO, BOD, COD and PO4 values that met water quality standards, except at station 3 which had very high BOD and COD values, presumably due to disposal of construction waste and household waste. For residential areas, only high BOD content exceeds the water quality standard. Whereas in the factory area, low DO levels indicate that it is not feasible for aquatic biota life. The BOD content is high at all stations, the COD content is very high only at station 2, which is indicated by the large amount of water hyacinth that grows and a very strong odor. In general, the water quality of the Cisadane River in three types of land use needs special handling to prevent environmental pollution.Keywords: water quality standards, water quality, Cisadane River, chemical properties, land use